Answer: 7
Step-by-step explanation:
To find the distance between the two point, we simply use this formular:
D = √ (x₂ -x₁)² + (y₂ - y₁ )²
x₁ = -4 y₁ =3 x₂=-4 y₂ = -4
D = √(-4-[-4])² + (-4-3)²
(-4-[-4])²= (-4+4)²=(0)²=0
(-4-3)² = 49
D = √0+49
D= √49
The square root of 49 is 7
D=7
Therefore the distance between (-4 3) and (-4 -4) is 7
Answer:
0.25 i
Step-by-step explanation:
0.25 i is the square root.
Answer:
EF, ED, EG and EA
Step-by-step explanation:
We know that, a ray is a line segment having one end point and reaches infinity on the other side.
It is required to find rays having E as an end point.
So, we can see from the figure that,
EF, ED, EG and EA are the four rays having E as an end point.
EB is not a ray as it has two end point, which is not possible in a ray.
Hence, we have that four rays having E as end point are EF, ED, EG and EA.
Answer:
what the other person said is correct
Step-by-step explanation: